2021
DOI: 10.1039/d1sc04833c
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly pure miktoarm spherical nucleic acids: preparation and usage as a scaffold for abiotic intracellular catalysis

Abstract: Biocompatible nano-constructs, with definite molecular structures and programmable subunits, can potentially be used as biocatalysts with modular functional moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For Cu-MAC IF catalysis, the incubation Cu concentration needed could be as low as 1 μM, while the reported Cu concentration for successful intracellular CuAAC using small molecular Cu-TTA analog was at the millimolar level ( 30 ). Therefore, it can be seen that despite MAC IF needs to face GSH and other coordinating molecules in the cytosol, the negatively charged phosphates on the cell membrane and those embedded membrane proteins might have provided sheltering for these catalysts ( 31 , 32 ). By incubating HeLa cells with FLip bearing FITC-labeled TTA-Cu II catalyst, we observed that the Cu-MACs immobilized via the LiFT process were able to stay on the cell membrane for an extended time period, showing a high extent of membrane staining even after 48 hours with well-preserved catalytic activity (fig.…”
Section: Resultsmentioning
confidence: 99%
“…For Cu-MAC IF catalysis, the incubation Cu concentration needed could be as low as 1 μM, while the reported Cu concentration for successful intracellular CuAAC using small molecular Cu-TTA analog was at the millimolar level ( 30 ). Therefore, it can be seen that despite MAC IF needs to face GSH and other coordinating molecules in the cytosol, the negatively charged phosphates on the cell membrane and those embedded membrane proteins might have provided sheltering for these catalysts ( 31 , 32 ). By incubating HeLa cells with FLip bearing FITC-labeled TTA-Cu II catalyst, we observed that the Cu-MACs immobilized via the LiFT process were able to stay on the cell membrane for an extended time period, showing a high extent of membrane staining even after 48 hours with well-preserved catalytic activity (fig.…”
Section: Resultsmentioning
confidence: 99%